The cyanide ligands of [FeFe] hydrogenase: pulse EPR studies of (13)C and (15)N-labeled H-cluster. - Myers, W; Stich, T; Suess, D; Kuchenreuther, J; Swartz, JR; Britt, R (American Chemical Society, 2014)
The two cyanide ligands in the assembled cluster of [FeFe] hydrogenase originate from exogenous l-tyrosine. Using selectively labeled tyrosine substrates, the cyanides were isotopically labeled via a recently developed in vitro maturation procedure allowing advanced electron paramagnetic resonance techniques to probe the electronic structure of the catalytic core of the enzyme. The ratio of the isotropic (13)C hyperfine interactions for the two CN(-) ligands-a reporter of spin density on their respective coordinating iron ions-collapses from ≈5.8 for the Hox form of hydrogenase to <2 for the CO-inhibited form. Additionally, when the maturation was carried out using [(15)N]-tyrosine, no features previously ascribed to the nitrogen of the bridging dithiolate ligand were observed suggesting that this bridge is not sourced from tyrosine.